Simultaneous determination of 101 volatile organic compounds released from plastic runway tracks based on the environmental chamber-canister sampling-three-stage cold trap preconcentration-gas chromatography-mass spectrometry/flame ionization detection method - Gan Liu; Gan Liu; Yong Ma; Yong Ma; Hong Wang; Hong Wang; Yanrong Meng; Yanrong Meng; Yu Huang; Yu Huang; Weitao Zheng; Weitao Zheng (Frontiers in Chemistry, 2025)
This paper provides a strategy for detecting and monitoring volatile organic compounds released from plastic runway tracks. The method applies a simultaneous determination of 101 VOCs based on the environmental chamber-canister sampling-three-stage cold trap preconcentration-gas chromatography-mass spectrometry/flame ionization detection (GC-MS/FID) method. For this purpose, an environmental chamber, SUMMA canisters, an atmospheric pre-concentrator, and a GC-MS/FID dual detection setup were adopted to collect VOCs released from plastic athletic tracks in an environmental chamber, followed by their preconcentration in a three-stage cold trap including glass-bead cold trap concentration, Tenax tube cold trap concentration, and capillary glass tube absorption focusing. Qualitative and quantitative analyses of VOCs were conducted. The obtained results showed that the optimal environmental parameters for releasing VOCs from plastic runway tracks were an ambient temperature of 60°C, a relative humidity of 5%, an air exchange rate of 1.0 h−1, and a release time of 24 h. The established method showed a linear relationship within a range from 0.8 to 16.0 ppb, with linear correlation coefficients for different compounds ranging from 0.9546 to 1.0000. The detection limits of the method ranged from 0.01 to 0.74 μg·m−3 (equivalent to 0.005–0.220 ppb, at 60°C and 1 atm), the relative error (n = 7) was between −10.16% and 12.84%, and the relative standard deviation (n = 7) was from 0.16% to 4.94%. The released VOCs can be divided into seven categories, including alkanes, alkenes, alkynes, aromatic hydrocarbons, halogenated hydrocarbons, oxygenated organic compounds, and nitrogenous organic compounds. Acetone (Z)-1,2-dichloroethene, 3-methylheptane, n-octane, n-decane, n-butane, trans-2-pentene, styrene, and 1,1,2,2-tetrachloroethane were common VOCs contained in athletic plastic tracks. The established simultaneous determination of VOCs based on the environmental chamber-canister sampling-three-stage cold trap preconcentration-GC-MS/FID method showed good linear and correlation relationships, high sensitivity and precision, and strong repeatability, which is suitable for the qualitative and quantitative detection of 101 kinds of VOCs from plastic athletic tracks. Finally, it was concluded that small differences in the mass concentration of the main VOC monomers appear in different athletic plastic tracks.